1997
DOI: 10.1021/es960645s
|View full text |Cite
|
Sign up to set email alerts
|

Surface Exchange and Transport Processes Governing Atmospheric PCB Levels over Lake Superior

Abstract: Measurements of gas phase PCB concentrations obtained at a site on the shore of Lake Superior are analyzed to determine the importance of regional air/surface exchange as a determinant of PCB concentration over the lake. During periods of onshore flow, results obtained in congenerspecific regression analyses of log concentration against reciprocal temperature are strongly dependent upon time of year. During months when the lake is colder than the overlying air (resulting in a stable atmosphere over the lake), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 37 publications
3
45
1
3
Order By: Relevance
“…It has been shown that the gas-phase air concentrations of SOCs have a strong relationship to ambient temperature (Lee and Jones, 1999;Cortes et al, 1998;Hoff et al, 1998;Honrath et al, 1997). As the temperature rises, gas-phase air concentrations increase as a result of volatilization from surfaces such as soil, atmospheric particles, water, and vegetation.…”
Section: Effect Of Meteorological Parameters On Gas-phase Ocp Concentmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the gas-phase air concentrations of SOCs have a strong relationship to ambient temperature (Lee and Jones, 1999;Cortes et al, 1998;Hoff et al, 1998;Honrath et al, 1997). As the temperature rises, gas-phase air concentrations increase as a result of volatilization from surfaces such as soil, atmospheric particles, water, and vegetation.…”
Section: Effect Of Meteorological Parameters On Gas-phase Ocp Concentmentioning
confidence: 99%
“…As the temperature rises, gas-phase air concentrations increase as a result of volatilization from surfaces such as soil, atmospheric particles, water, and vegetation. The temperature dependence of gas-phase ambient concentrations of SOCs has been investigated using ClausiusClapeyron plots (Lee and Jones, 1999;Cortes et al, 1998;Hoff et al, 1998;Honrath et al, 1997;Hillery et al, 1997) and surface exchange models (Wania et al, 1998).…”
Section: Effect Of Meteorological Parameters On Gas-phase Ocp Concentmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the air concentrations of semivolatile organic compounds (SOCs) have a strong relationship to ambient temperature (Lee and Jones, 1999;Cortes et al, 1998;Hoff et al, 1998;Honrath et al, 1997). As the temperature rises, air concentrations increase as a result of volatilization from surfaces such as soil, atmospheric particles, water, and vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…As the temperature rises, air concentrations increase as a result of volatilization from surfaces such as soil, atmospheric particles, water, and vegetation. The temperature dependence of gas-phase ambient concentrations of SOCs has been investigated using ClausiusClapeyron plots (Lee and Jones, 1999;Cortes et al, 1998;Hoff et al, 1998;Honrath et al, 1997;Hillery et al, 1997) and surface exchange models (Wania et al, 1998). The variation in atmospheric SOC concentrations can be quantified using the Clausius-Clapeyron equation…”
Section: Introductionmentioning
confidence: 99%